Combined variants in factor VIII and prostaglandin synthase‐1 amplify hemorrhage severity across three generations of descendants. (20th October 2016) - Nance, D.; Campbell, R. A.; Rowley, J. W.; Downie, J. M.; Jorde, L. B.; Kahr, W. H.; Mereby, S. A.; Tolley, N. D.; Zimmerman, G. A.; Weyrich, A. S.; Rondina, M. T.
Abstract : Essentials Co‐existent damaging variants are likely to cause more severe bleeding and may go undiagnosed. We determined pathogenic variants in a three‐generational pedigree with excessive bleeding. Bleeding occurred with concurrent variants in prostaglandin synthase‐1 (PTGS‐1) and factor VIII. The PTGS‐1 variant was associated with functional defects in the arachidonic acid pathway. Summary: Background: Inherited human variants that concurrently cause disorders of primary hemostasis and coagulation are uncommon. Nevertheless, rare cases of co‐existent damaging variants are likely to cause more severe bleeding and may go undiagnosed. Objective: We prospectively sought to determine pathogenic variants in a three‐generational pedigree with excessive bleeding. Patients/methods: Platelet number, size and light transmission aggregometry to multiple agonists were evaluated in pedigree members. Transmission electron microscopy determined platelet morphology and granule content. Thromboxane release studies and light transmission aggregometry in the presence or absence of prostaglandin G2 assessed specific functional defects in the arachidonic acid pathway. Whole exome sequencing (WES) and targeted nucleotide sequence analysis identified potentially deleterious variants. Results: Pedigree members with excessive bleeding had impaired platelet aggregation with arachidonic acid, epinephrine and low‐dose ADP, as well as reduced platelet thromboxane B2 release. Impaired platelet aggregation in response to 2MesADP was rescued with prostaglandin G2, a prostaglandin intermediate downstream of prostaglandin synthase‐1 (PTGS‐1) that aids in the production of thromboxane. WES identified a non‐synonymous variant in the signal peptide of PTGS‐1 (rs3842787; c.50C>T; p.Pro17Leu) that completely co‐segregated with disease phenotype. A variant in the F8 gene causing hemophilia A (rs28935203; c.5096A>T; p.Y1699F) was also identified. Individuals with both variants had more severe bleeding manifestations than characteristic of mild hemophilia A alone. Conclusion: We provide the first report of co‐existing variants in both F8 and PTGS‐1 genes in a three‐generation pedigree. The PTGS‐1 variant was associated with specific functional defects in the arachidonic acid pathway and more severe hemorrhage.